PEMBUATAN KEPUTUSAN DALAM KEADAAN RESIKO OLEH KEPALA SEKOLAH - Iskandar Iskandar (UNIVERSITAS BENGKULU, 2015)
This study aims at describing the decision making of risk problem made by the principal. This study is descriptive qualitative which uses questionnaire, interview and documentation as the data and analyze use qualitative analysis, percentage and scoring. This study concludes that (a) principal identifies problems; formulates the goals of decision making; arranges the solution possibilities, gives solution criterions of each solution possibilities and takes one of them as the final decision, (b) principal tends to apply the brain storming and synetics techniques and (c) principal tends to use conceptual style in the decision making process.Keywords: decision making, principal, risk problem